Experimental and computational investigation of a nose-only exposure chamber. Issue 3 (3rd March 2020) - Lucci, Francesco; Tan, Wei Teck; Krishnan, Subash; Hoeng, Julia; Vanscheeuwijck, Patrick; Jaeger, Rudolph; Kuczaj, Arkadiusz
Abstract: Inhalation exposure chambers may be used for in vivo drug delivery or toxicological assessments among other applications. Nose-only exposure chamber (NOEC) systems limit non-respiratory aerosol exposure pathways that may affect biological response analyses in mice. Uniform aerosol delivery between all ports is desired, but any exposure system design may introduce variability. The aerosol flow characteristics in a commercially available NOEC system were assessed computationally and experimentally to estimate the particle size-dependent non-uniformities of the aerosol sampled at each exposure port. Only dilute non-evolving aerosols are considered in the present study. The experimental measurements recorded a flow velocity variability of up to 20% between ports. Sampling variability between ports was experimentally verified to be within 10% for particles >0.56 µm and <1.7 µm at controlled velocity dictated by the animal's respiratory flow rate. This smaller particle number density variability at the exposure port was also predicted computationally. Main source of flow variability was associated to a recirculation inside the inner plenum. Sedimentation of larger particles (>3 µm) was observed inside the ports, causing visible aerosol separation on the top of the channel delivering the aerosol to the exposure trumpet. As the effect was minor and applied to particles beyond the size range recommended for mouse inhalation studies, it should have no influence on the dosimetry of inhaled aerosols. In the range of aerosol particle sizes and flow rates considered, a good agreement between computational and experimental results was found, confirming the suitability of the system for mouse inhalation studies, and the insights obtained may give rise to further improvements in the system design.